Towards a nationally pertinent system of knowledge, science, and technology - Aguilar Castro, J. (2015)
This chapter describes an autochthonous system of Knowledge, Science, and Technology (KST): its actors, policies, strategies, and instruments. It is proposed to create it via a continuous reflection-action process. Such a system is aimed at promoting an autonomous nation, and will strongly rest on culturally free KST, beyond its actual conception (as universally valid, and neutral) in the Western Society. We argue that since the culture, problems and needs of the western nations are different from those of the non-western nations, such as Latinamerica, Africa or the Muslim World, the use of western KST in non-western societies without an appropriate reflection about national and local pertinence, generates dependence on KST that has very limited local societal benefits, and prevents developing an autonomous and pertinent KST system - non-western societies can only superficially capture the creations of the western society. To overcome this, we suggest that non-western nations must generate an autochthonous KST system. 2015 by IGI Global. All rights reserved.